New species of lizard from the magellanicus clade of the Liolaemus lineomaculatus section (Squamata: Iguania: Liolaemidae) from southern Patagonia - Breitman, Maria Florencia; Pérez, Cristian Hernán Fulvio; Parra, Micaela; Morando, Mariana; Sites, Jr., Jack Walter; Avila, Luciano Javier (Zootaxa, 2011)
A new species of the Liolaemus lineomaculatus section is described from southwestern Santa Cruz Province, Argentina. The new species is a member of the monotypic magellanicus clade; morphological, molecular and geographical data are sufficient to diagnose this new species as distinct form from L. magellanicus. The new species differs from L. magellanicus in having higher number of midbody, dorsal and ventral scales, and higher number of infradigital third finger and fourth toe lamellae. The new species also differs in having smaller dorsal blotches on the hindlimbs and a more clearly defined vertebral line, fewer precloacal pores and reduced dorsal scale mucronation, compared to L. magellanicus. Liolaemus caparensis sp. nov. is the second species described for the magellanicus group, and is geographically isolated from L. magellanicus on the Campo Las Piedras Plateau, where it is sympatric with other endemic species of the L. lineomaculatus section.